Supporting the development of effective and efficient river basin arganizations in Asia: a discussion of the application of organizational benchmarking approaches. Draft - Makin, Ian W.; Parks, Y. P.; Arriens, W. L. (2004)
The initial work plan for the newly formed Network of Asian River Basin Organizations (NARBO) identified the development of systematic methods to support the development of effective stakeholder driven river basin organizations as one of NARBO’s priority activities. The Asian Development Bank (ADB) and the International Water Management Institute (IWMI) agreed to lead the investigation and development of appropriate supporting tools in collaboration with members of NARBO. This document is presented to facilitate discussions at stakeholder workshops amongst NARBO members. The paper is structured with a brief overview of the rapid development of river basin organizations in response to the international efforts to increase stakeholder involvement in river basin management (section 1); an introduction to the concepts and approaches to performance management introducing benchmarking and peer review (section 2); an expanded discussion of benchmarking approaches proposed as applicable to river basin organizations (section 3); and a model for the development and implementation of a comprehensive benchmarking service for use by river basin organizations that seeks to improve the efficiency and effectiveness of their service delivery (section 4). Section five summarizes the discussions and presents brief conclusions. The draft report includes three annexes. Annex 1 discusses the objectives of the inclusion of Peer Review as a core component of the Benchmarking initiative. Annex 2 presents a outline functional specification for a demonstration implementation of a web-enabled benchmarking service. Annex 3 presents examples of Performance indicators used in the Irrigation benchmarking service and also the Common Assessment Framework.